Pengaruh Penggunaan Fly Ash dan Bottom Ash Sebagai Bahan Dalam Pembuatan Baterai Terhadap Kinerja dan Efisiensi Energi - maulana, arif; Putri, Novia Utami; Dalimunthe, Ernando Rizki; Pranita, Elka (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
Fly ash and bottom ash are one of the problems of energy companies because their production is abundant, but their disposal and processing are not yet optimal. The use of fly ash and bottom ash is processed so that it does not have a negative impact on the environment, one way is by using fly ash and bottom ash as materials in making batteries. Burning coal produces fly ash solid waste which contains 39.70% carbon (C) and 46.99% silicon dioxide (SiO2). This research is research using an experimental research approach. Experimental research can be interpreted as research that is carried out to find out the consequences of a treatment that is deliberately given by the research. Processing coal waste in the form of fly ash and bottom ash as an alternative source of electrical power can be an alternative choice for reducing the amount of coal ash waste that accumulates in PLTUs. is in Indonesia. The battery consists of electrodes made from a mixture of fly ash and bottom ash which are mixed using salt water, MSG and electrolyte. Of the three mixtures that have been experimented with, a good mixture is a mixture of fly ash and bottom ash with an electrolyte mixture that gets a voltage of 1,133 volts and a current of 0.111 Ampere.